Neuromarketing Study: The Effect of Jingle on Consumer Behavior - Fauzi, Hilman; Rizqullah, Rafif; Ariyanti, Maya; Hadyningtyas, Ivy Anindhita (ASEAN Marketing Journal, 2022)
Manuscript type: Research Article Research Aims: This research investigates the impact of a jingle associated with a top-brand product on consumer behavior, as assessed through short-term memory activity in the brain. Design/methodology/approach: Data were collected from six participants, three men and three women aged 19-24. The Contec KT88-1016 Digital 16-Channel EEG machine and the Mapping System device were used to retrieve the data. The channel selection was employed to identify the optimal channel based on L2-norm energy calculations performed on the EEG channels within the short-term memory area. Research Findings: The frontal area exhibited higher energy levels than other areas, with the highest point observed in channel F4. A jingle in a product was found to stimulate short-term memory, influencing consumer behaviour. This influence was evidenced by the representation of channel energy in the EEG, showing a higher value compared to the average energy value in general. Theoretical Contribution/Originality: This study successfully demonstrated that EEG signals stimulated by jingles could assess consumer behaviour responses when provided with auditory incentives. The findings are explicitly linked to activating the brain's short-term memory area. Practitioner/Policy Implication: Brands with top brand categories have higher signal energy than non-top brands. Research limitation/Implications: Only limited to the data collection process carried out by environmental engineering, which is made closer to the actual situation.